The value of graduated compression socks as a post-exercise recovery modality in long distance runners - Welman, Karen Estelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Sport Sc) (Sport Science))--University of Stellenbosch, 2011.